Faktor-Faktor yang Memengaruhi Empati Siswa di Sekolah Inklusi - Risma Yanti, Gita; Susilawati, Pande Ary (JPI (Jurnal Pendidikan Inklusi), 2022)
Inclusive education is a form of educational equality in Indonesia that aims to overcome various educational problems for Children with Special Needs (ABK) who carry out learning activities through public or regular schools by using existing resources to create opportunities for their preparation for life in society. In its implementation, there are problems in inclusive education due to the lack of empathy between regular and ABK students. Empathy is the ability to understand other people's feelings. Increasing empathy needs to be a priority in creating optimal inclusive education. The method used in this research is a literature review. This literature review aims to see what factors influence regular students' empathy towards students with special needs in inclusive schools. The review was carried out on an online database, namely Google Scholar, on 8 articles based on inclusion criteria. The results of the literature research show that there are factors that influence regular students' empathy towards ABK students, namely social support, perception, teacher communication strategies, school-based educational interventions, level of education and gender, child-friendly learning programs, group guidance using photovoice techniques, and psychodrama.